Peran Hakim Terhadap Penerapan Diversi Sebagai Upaya Menciptakan Restoratif Justice Dalam Tindak Pidana Anak - Esther Wita Simanjuntak; Madiasa Ablisar; Sutiarnoto Sutiarnoto; Marlina Marlina (Iuris Studia: Jurnal Kajian Hukum, 2021)
In Law No. 11 of 2012 concerning the Juvenile Criminal Justice System, it is regulated regarding the obligations of law enforcers to seek diversion (settlement through non-formal channels) before entering all stages of the legal process. For cases of criminal acts committed by children, Restorative Justice at least aims to repair or restore criminal acts committed by children with actions that are beneficial to children, victims and their environment that involve them directly (reintegration and rehabilitation) in solving problems. This research is a normative juridical research with analytical descriptive nature. The technique of collecting secondary data was obtained by means of a literature review (Library Research), while the primary data was obtained directly in the field using the interview method. Data analysis was carried out qualitatively.